Editorial - Zeta de Pozo, Rosa (2019)
The world of Communication is complex, due to the changing environment in which it is located and, essentially, due to technological disruption and its impact on today's digital society. In this eminently technological context, the ideal use and exploitation of its tools for the benefit of society is of concern. Generally, we accept free access to information in the Internet era, but we are worried about the use of algorithms that give direction to that information, and that is not as plural as it seems; or that it can even be false, without being detected. There are doubts about the quality of information, the privacy of our data and security. Companies, states and audiences are taking measures: Facebook will hide the number of likes of its accounts; Users are more cautious with their data; Google, Facebook and Twitter have been invited by the Federal Election Commission to explore ways to combat digital misinformation in the 2020 elections.